Office‐based transnasal esophagoscopy biopsies for histological diagnosis of head and neck patients. (13th December 2018) - Mohammed, Hassan; Del Pero, Marcus; Coates, Matthew; Masterson, Liam; Tassone, Peter; Burrows, Stuart; Nassif, Ramez
Abstract : Objectives/Hypothesis: To present yield of transnasal esophagoscopy (TNE) biopsies of upper aerodigestive tract (UADT) lesions and define the role of TNE as a safe alternative to rigid endoscopy. Study Design: Retrospective case series. Methods: All patients who underwent TNE‐guided biopsies attempted over a 2‐year period were included. Patients were identified using coding records and outpatient diaries. Demographic data were recorded as well as the histological diagnosis and additional histological diagnostic procedures. Results: During the observation period, 134 TNE‐guided procedures were attempted. The procedure could not be completed in 19 patients. There were 102/115 (89%) patients who did not require further interventions for histological diagnosis of the tumor. The most common biopsied area was the larynx (53), followed by the tongue base (29). The most common malignancy was invasive squamous cell carcinoma in 42/115 (36.5%). Conclusions: The work presented in this article strongly suggests that TNE‐guided biopsy is a valuable diagnostic tool for patients suspected of having carcinoma of the UADT. Level of Evidence: 4 Laryngoscope, 129:2721–2726, 2019